The great divergence: a network approach - Lindner, Ines; Strulik, Holger (Munich, 2015)
"We present a multi-country theory of economic growth in which countries are connected by a network of mutual knowledge exchange. Knowledge in any country depends on the human capital of the countries it exchanges knowledge with. The diffusion of knowledge throughout the world explains a period of increasing world inequality after the take-off of the forerunners of the industrial revolution, followed by decreasing relative inequality. Knowledge diffusion through a Small World network explains the ‘New Kaldor facts’ and produces an extraordinary diversity of country growth performances, including the overtaking of individual countries in the course of world development."